Novel Design of Power Position Control Feedback System in MATLAB (International Journal of Innovative Research in Engineering & Management, 2021)
Motor position control is employed in a variety of settings,  including the workplace, the home, and manufacturing plants.  The motor load is expected to account for about 70% of total  electrical consumption. The motors utilised in this section have  been used for a wide range of tasks, including traction loads,  rotating machines, and position control. Printing heads in  printers, hoist motors, 3D printers, CNC machines, and even  more modern robotic surgical equipment use position controlled motors to communicate with the environment are all  examples of position control. Position control is simply  defined as a motor with a position encoder, such as a resistive  encoder or an optical encoder that gives control signals to the  controller, and a controller that regulates the power supplied to  the motor using a power controller, such as a DC-DC  regulator. In this project position control of a DC motor is  done by using the Proportional-Integral-Derivative (PID)  approach in Simulink. PID attempts to fix the disparity by  calculating the error between the actual and desired locations  and then creating a PWM (pulse width modulated) signal by  which position can be adjusted. The system changes into a  closed-loop when a PID algorithm is applied to it. Error  developed by the DC motor as well as the motor's orientation  can be corrected to the desired position when PID controller is  combined with DC motor. The PID values Kp, Ki, and Kd are  fine-tuned using Z. Nichols principles and the t&e approach,  and to manage the direction of the DC motor using optimum  values the PID algorithm is fine-tuned.
Keywords: Controller( PID); Closed Loop; Open Loop